2015
DOI: 10.1002/hep.27593
|View full text |Cite|
|
Sign up to set email alerts
|

CCAAT/enhancer binding protein α predicts poorer prognosis and prevents energy starvation–induced cell death in hepatocellular carcinoma

Abstract: CCAAT enhancer binding protein α (C/EBPα) plays an essential role in cellular differentiation, growth, and energy metabolism. Here, we investigate the correlation between C/EBPα and hepatocellular carcinoma (HCC) patient outcomes and how C/EBPα protects cells against energy starvation. Expression of C/EBPα protein was increased in the majority of HCCs examined (191 pairs) compared with adjacent nontumor liver tissues in HCC tissue microarrays. Its upregulation was correlated significantly with poorer overall p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 33 publications
1
67
0
1
Order By: Relevance
“…We showed that HCC cells with a high level of lipid content displayed a survival advantage against nutrient starvation. Similar to our findings, it has been reported that autophagy‐mediated lipid metabolism is linked to resistance to energy starvation in HCC carcinogenesis . Cellular stress, including nutrient deficiency, facilitated lipid droplet biosynthesis and mobilization, which was required for fueling FAO to maintain cells survival under these conditions .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We showed that HCC cells with a high level of lipid content displayed a survival advantage against nutrient starvation. Similar to our findings, it has been reported that autophagy‐mediated lipid metabolism is linked to resistance to energy starvation in HCC carcinogenesis . Cellular stress, including nutrient deficiency, facilitated lipid droplet biosynthesis and mobilization, which was required for fueling FAO to maintain cells survival under these conditions .…”
Section: Discussionsupporting
confidence: 90%
“…Alternations of ACCα had no impact on autophagic flux, as revealed by conversion of LC3B‐II and degradation of SQSTM1 in hepatoma cells during both glucose and glutamine starvation (http://onlinelibrary.wiley.com/doi/10.1002/hep.28415/suppinfo). More important, pharmacological inhibition of autophagy with chloroquine (CQ) further increased starvation‐stimulated LC3B‐II amounts, regardless of ACCα expression levels in hepatoma cells (http://onlinelibrary.wiley.com/doi/10.1002/hep.28415/suppinfo). Thus, it seemed that ACCα regulated lipid metabolism and protected HCCs against starvation in an autophagy‐independent manner.…”
Section: Resultsmentioning
confidence: 99%
“…Expression of CEBPA protein was increased in HCCs [35], and epigenetic aberrations in regulating CEBPA expression contributed to leukemic transformation in acute myeloid leukemia[36]. INHBA mRNA and protein expression is commonly elevated in primary human NSCLC, and it promotes tumor metastasis [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, active fatty acid oxidation in the resistant HCC cells can protect cells with necessary ATP generation even if the exogenous glucose is unavailable and the endogenous glycogen is depleted. The author recently confirmed this hypothesis by comparing the starvation-sensitive with -resistant HCC cells [81]. The results demonstrated that the sensitive HCC cells, lack of an important transcription factor C/EBPalpha, could not initiate fatty acid oxidation and died within 12 h during enforced glucose deprivation in vitro.…”
Section: Lipid Catabolism In Liver Cancer: a Potential Therapeutic Tamentioning
confidence: 86%